AB0400 High Prevalence of Vitamin D Deficiency and Insufficiency in Patients with Either Rheumatic or Inflammatory Bowel Diseases. (9th June 2015) - Bruzzese, V.; Ridola, L.; Zullo, A.; Hassan, C.; Lorenzetti, R.; Severino, M.L.; Scolieri, P.; Marrese, C.; Picchianti Diamanti, A.; Laganà, B.
Abstract : Background: Vitamin D deficiency has been reported in patients with chronic inflammatory conditions, such as rheumatic and inflammatory bowel diseases (IBD). Objectives: To assess vitamin D status in patients with either rheumatic or IBD, receiving biologic or disease-modifying antirheumatic drugs (DMARDs) therapies. Methods: In this cross-sectional study, serum vitamin D of consecutive patients were measured. Patients receiving vitamin D supplementation were excluded. Vitamin D levels >30 ng/mL (75 nmol/L) were considered normal, insufficiency is defined as a concentration of 20 to 30 ng/mL (50 to 75 nmol/L), and deficiency when levels were <20 ng/mL (50 nmol/L). Results: A total of 181 patients, including 136 with rheumatic (M/F: 36/100; Median age: 60 years, range 26-84; Rheumatoid arthritis: 87; Psoriatic arthritis: 38; Ankylosing spondilitis: 8; Polymyalgia rheumatica: 3) and 45 with intestinal diseases (M/F: 30/15; Median age: 52 years, range 32-68; Crohn's disease: 24; Ulcerative colitis: 21) were enrolled. A total of 119 patients were receiving biologic therapy and 62 DMARDs. Vitamin D deficiency/insufficiency was detected in as many as 84 (61.8%) and in 34 (75.6%) patients with rheumatic disease or IBD, respectively. IBD patients showed significantly lower vitamin D levels than rheumatological patients (28.7±19.1 vs 22.5±10.3; P<0.01). Among rheumatic disease patients, the prevalence of Vitamin D deficiency (50.7% vs 29.5%; p=0.01), insufficiency (28% vs 11.5%; p=0.02), and deficiency-insufficiency (78.7% vs 41%; p<0.001) was significantly higher in patients receiving biologic therapy than in those treated with DMARDs. Conclusions: Prevalence of Vitamin D deficiency/insufficiency was very high in both rheumatic disease and IBD patients, particularly in those receiving a biologic therapy. Vitamin D levels should be investigated also in IBD patients, the deficiency being even more frequent than in rheumatic disease patients. Disclosure of Interest: None declared